Preparation method and application of sodium alginate composite fiber containing nano-activated carbon
By introducing nanoactivated carbon into sodium alginate fibers and optimizing the fiber preparation process, the problems of loose structure and insufficient mechanical properties of sodium alginate fibers are solved, and higher mechanical properties and biocompatibility are achieved, and its application potential in the field of medical materials has been expanded.
Patent Information
- Application Number
- CN202111295683.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-11-03
AI Technical Summary
The structure of sodium alginate fiber material is loose, swells and easily ruptured, lacks strength and elasticity, and is difficult to achieve complex three-dimensional structures and high mechanical strength, which limits its processing performance and application range.
Compound fibers of nanoactivated carbon and sodium alginate were prepared by injection wet spinning process. The mechanical properties of sodium alginate fibers were enhanced by nanoactivated carbon, and the concentration of sodium alginate solution and calcium ion concentration were optimized to improve the stability and biocompatibility of the fibers.
The prepared sodium alginate composite fiber containing nano activated carbon has significantly improved mechanical properties, biocompatibility, stability and safety, and is suitable for cell packaging and medical materials fields.
Smart Images

Figure CN113969435B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium alginate fibers, in particular to a preparation method of sodium alginate composite fibers containing nano-activated carbon and application thereof. Background Art
[0002] Sodium alginate (SA) is a water-soluble anionic natural polysaccharide with good biocompatibility, biodegradability, non-toxicity, and the ability to provide cell recognition sites. It is often used as a biomedical material in the medical field. SA can be chelated and cross-linked with multivalent metal cations to form various materials such as gel, film, microcapsule or fiber. Among them, sodium alginate fiber can be processed into fabrics, non-woven fabrics and various medical composite materials due to its unique structural properties, such as hemostatic materials, healing materials, tissue engineering scaffolds and drug release materials. However, since SA is a linear molecular chain, the chains cannot be effectively entangled, making the alginate fiber material loose in structure, easy to rupture when swollen, and lacking in strength and elasticity. It is difficult to achieve a complex three-dimensional structure and high mechanical strength, which greatly affects its processing performance and wider application.
[0003] In recent years, studies have found that SA nanocomposites obtained after adding nanomaterials have many unique physical and chemical properties. Carbon materials, as the most widely used materials on earth, have always been the focus of scientific research. Up to now, there have been a large number of reports on carbon nanomaterials modified alginate fibers, such as carbon nanofibers, carbon nanotubes, cellulose nanocrystals or graphene oxide nanosheets, which can enhance the mechanical properties of alginate fiber materials. There are also reports on the use of activated carbon as a carbon material composite SA, but they all focus on the adsorption capacity of activated carbon, and there are few reports on the application of nano-scale activated carbon modified alginate fiber performance in medical materials.
[0004] Active carbon nanoparticles (ACNP) are low-toxic, highly biocompatible carbon materials with strong drug adsorption and sustained-release properties. Clinically, it is often used as an indicator of lymphatic drainage and a drug sustained-release agent. It is also the only carbon material currently used in clinical practice. Therefore, from the perspective of medical materials, the performance of nano-activated carbon-modified alginate fiber materials is worth exploring. However, with the in-depth study of nanomaterials, the potential hazards of carbon nanomaterials to human health have attracted people's attention. Studies have reported that short carbon nanofibers are toxic to fibroblasts and can reduce cell viability. The length threshold of their toxicity is about 189±17nm.
[0005] In summary, there has been no substantial progress in the application of nano-activated carbon to alginate fibers, and the performance of the product is unknown.
[0006] Cell encapsulation technology refers to wrapping cells in a translucent encapsulation matrix. This technology has important application value in many fields such as cell therapy, cell transplantation, cell storage / transportation, cell analysis, tissue engineering and regenerative medicine.
[0007] In 1980, Anthony M Sum et al. used droplet formation technology combined with the cross-linking reaction between sodium alginate and calcium chloride, polylysine (PLL), and polyethyleneimine (PED) to prepare pancreatic islet microcapsules for the first time, and implanted them into the abdominal cavity of diabetic rats induced by streptozotocin. The results showed that the implanted pancreatic islet microcapsules could effectively reduce the blood glucose level of diabetic rats within 2 to 3 weeks; in addition, long-term cell culture experiments found that the pancreatic islet microcapsules could maintain their morphology and function intact for more than 15 weeks. In order to improve the biocompatibility of microcapsules, Anthony M Sun et al. subsequently established the preparation of sodium alginate-polylysine sodium alginate (APA) microcapsules. At the same time, researchers have successively achieved the encapsulation of hepatocytes, hybridoma cells, kidney cells, genetically modified cells, and the co-encapsulation of multiple cells.
[0008] One of the characteristics of an ideal encapsulation material is that it is completely inert and does not cause immune response or peripapular fibrosis (PFO) in the recipient of allogeneic transfer. Although improvements to sodium alginate and other encapsulation materials in the prior art have reduced PFO and increased the survival rate of transplanted cells, Kamperman T et al. pointed out in "Single-cell microgels: Technology, challenges, and applications" published in "Trends Biotechnol" that sodium alginate materials do not have any specific biological signals and responses to animal cells, making it difficult to maintain the normal activity and growth of encapsulated cells.
[0009] It can be seen that sodium alginate materials still have defects in cell viability, biocompatibility and other aspects when used for cell encapsulation. Summary of the invention
[0010] The object of the present invention is to provide a method for preparing sodium alginate composite fibers containing nano-activated carbon, wherein the obtained alginate fibers have good mechanical properties and biocompatibility as well as high stability and safety.
[0011] The design idea of the present invention is: to prepare composite fibers of nano-activated carbon and sodium alginate by injection wet spinning process, to enhance the mechanical properties of the sodium alginate composite fibers by nano-activated carbon, and to obtain products with better mechanical properties, stability, permeability and biocompatibility.
[0012] In order to achieve the above-mentioned object of the present invention, the present invention provides the following technical solutions:
[0013] As a first aspect of the present invention, a method for preparing a sodium alginate composite fiber containing nano-activated carbon is provided, comprising the following steps:
[0014] Step 1, dissolving sodium alginate powder in water, filtering and sterilizing, and setting aside to obtain a sodium alginate solution;
[0015] Step 2, sterilize the nano activated carbon and set aside;
[0016] Step 3, weighing the sterilized nano-activated carbon obtained in step 2 and dissolving it in the sodium alginate solution obtained in step 1 to prepare a mixed solution;
[0017] Step 4: adopt a wet spinning process to flow the mixed solution obtained in step 3 into a calcium chloride solution for calcification, and wash after the calcification is completed to obtain the product.
[0018] Preferably, the content of sodium alginate solution in step 1 is 1.5% to 3.0% (w / v), more preferably 2.5% (w / v).
[0019] Preferably, in step 2, the nano activated carbon is sterilized at 121° C. for 20 min.
[0020] Preferably, in step 3, the weight ratio of nano activated carbon to sodium alginate solution is (2-8):100, more preferably 2:100.
[0021] Preferably, the content of calcium chloride solution in step 4 is 1% to 3% (w / v), more preferably 1.5% (w / v).
[0022] Preferably, the particle size of the nano activated carbon is 50 to 300 nm, more preferably 200 nm.
[0023] Preferably, sodium alginate powder is weighed and dissolved in distilled water to prepare a 2.5% (w / v) sodium alginate solution, which is filtered and sterilized with a 0.45 μm filter for later use; at the same time, nano-activated carbon is sterilized at 121° C. for 20 min and set aside; the sterilized nano-activated carbon is weighed and dissolved in the sodium alginate solution to prepare a mixed solution, wherein the weight ratio of the nano-activated carbon to the sodium alginate solution is 2:100, and a wet spinning process is used to adjust the flow rate of the injection pump to flow the mixed solution into a 1.5% (w / v) calcium chloride solution for calcification for 15 min, and the alginate fiber is washed twice with distilled water to prepare alginate fibers.
[0024] Furthermore, the flow rate of the injection pump is 1000 μl / min.
[0025] The preparation of biomedical materials requires high stability, permeability and biocompatibility. In order to meet the above requirements, the effects of the concentration of sodium alginate solution and the concentration of calcium ions on the product were compared and studied.
[0026] Studies have found that sodium alginate hydrogel is significantly affected by concentration: at low concentrations, the permeability is high and the mechanical properties are low, which is not conducive to processing and utilization; at high concentrations, the solution viscosity is high, the mechanical properties increase but it is not conducive to the passage of substances; based on research and comparison, the present invention adopts a sodium alginate solution with a concentration of 1.5% to 3.0% (w / v). In view of the fact that the ultimate goal of this study is to prepare biomedical materials, which require higher stability, permeability and biocompatibility, 2.5% (w / v) is more preferred.
[0027] In addition, Ca 2+ The concentration has a great influence on the mechanical properties of the gel. 2+ When the concentration is low, the gel mesh pore size is large, the gel mechanical stability is poor, and it is easy to break, which is not conducive to use; Ca 2+ When the concentration is high, the gel structure is dense, the mass transfer performance is poor, and it is not conducive to the exchange of internal and external substances. According to experimental research and comparison, the present invention selects a calcium chloride concentration of 1.5%, which has low cytotoxicity and is conducive to gelation.
[0028] Prior art research has found that the mechanical properties of gel fibers prepared by pure sodium alginate molecules are poor. Although the mechanical properties of alginate fibers are improved by continuously adjusting the spinning process parameters, they still cannot meet their post-processing and use performance. The present invention selects nano-activated carbon as a reinforcement, and studies the effects of different addition concentrations on the performance of alginate fibers in the embodiments. It is found that with the increase of ACNP concentration, the light transmittance of alginate fibers deteriorates. At the same time, the results show that adding an appropriate amount of nano-activated carbon can significantly enhance the mechanical properties of alginate fibers, especially when the ratio of nano-activated carbon to sodium alginate solution is 2:100 to 4:100, the fiber elongation at break is much higher than other ratios, the fracture stress is higher, the swelling rate is high, and at the same time, it has better biostability and biosafety, and can be used as a medical material for encapsulating cells. At the same time, the present invention provides nano-activated carbon in a composite state, and the composite activated carbon material has a smaller particle size and better biocompatibility in vivo.
[0029] As a second aspect of the present invention, it is to provide a sodium alginate composite fiber containing nano-activated carbon prepared by the preparation method for cell encapsulation application. The cells include but are not limited to pancreatic islet cells, thyroid cells and parathyroid cells.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention provides a method for preparing sodium alginate composite fibers containing nano-activated carbon, and obtains ACNP / SA composite fibers with the best mechanical properties and biocompatibility;
[0032] 2. The present invention provides a new alginate composite fiber material. The surface of the prepared alginate fiber containing nano-activated carbon is smoother and tighter than that of pure alginate fiber, which solves the problem of groove defects in alginate fibers and helps to improve the mechanical properties of the fibers. The nano-activated carbon plays a certain supporting role on the alginate fibers, and is beneficial to increase the fiber porosity, reduce diffusion resistance, and enhance the permeability of the fibers.
[0033] 3. The present invention found that when the addition amount of nano activated carbon is between 0% and 2%, the elongation performance, breaking stress and swelling rate of alginate fiber increase simultaneously; when the addition amount of ACNP is 2%, the breaking elongation of the prepared alginate fiber is increased by 80.2% compared with the alginate fiber without addition, and the breaking stress increases by 42.5%;
[0034] 4. Compared with alginate fibers, after adding 2% and 4% ACNPs to alginate fibers, the extract showed better characteristics of supporting the growth of MIN6 cells; this shows that the ACNP / SA composite fiber is non-toxic to cells in vitro, has good cell compatibility and biosafety, and has development and application value in the field of medical materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0036] Figure 1 To observe the image with an inverted microscope,
[0037] Among them, Figure a.0% ACNP / SA, b.2% ACNP / SA, c.4% ACNP / SA, d.8% ACNP / SA are images at a magnification of 100; e.8% ACNP / SA is an image at a magnification of 200;
[0038] Figure 2 This is the surface morphology of sodium alginate composite fiber.
[0039] Among them, a. 0% ACNP / SA was observed under an inverted microscope at 10×; b. 0% ACNP / SA was observed under a scanning electron microscope; c. 2% ACNP / SA was observed under an inverted microscope at 10×; d. 2% ACNP / SA was observed under a scanning electron microscope;
[0040] Figure 3 is the swelling curve of sodium alginate composite fiber with different ACNP concentrations in normal saline;
[0041] Figure 4 This is a comparison chart of the effects of different sodium alginate composite fiber extracts on the growth of MIN6 cells.
[0042] Among them, from left to right at each time point are control group, 0% ACNP / SA, 2% ACNP / SA, and 4% ACNP / SA. DETAILED DESCRIPTION
[0043] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0044] It should be noted that the terms used herein are for describing specific embodiments only and are not intended to be limiting of exemplary embodiments according to the present invention.
[0045] Example 1, preparation of ACNP / SA composite fiber:
[0046] 1. Experimental Materials and Methods
[0047] 1.1 Reagents and instruments
[0048] Sodium alginate (MW: 100,000-200,000 g / mol, G Content: 65%-70%), Sigma Aldrich;
[0049] ACNP, 200nm, Shanghai Hainuo Carbon Industry Co., Ltd.;
[0050] CaCl2, AR, Tianjin Damao Chemical Reagent Factory;
[0051] The distilled water was double distilled water, homemade.
[0052] The MIN6 cell line was established from the pancreatic islet tumor of transgenic non-obese diabetic mice expressing simian virus 40 large T antigen (controlled by the insulin promoter). Its endocrine function is very similar to that of pancreatic tissue, making it an ideal model for studying the function of pancreatic islet cells. The MIN6 cells in this experiment were provided by the Department of Endocrinology of Qilu Hospital.
[0053] Regulus 8200 scanning electron microscope, Hitachi;
[0054] PHG-9140A drying oven, Shanghai Huitai Instrument Co., Ltd.;
[0055] LongerPump syringe pump, Hebei Baoding Lange Constant Flow Pump Co., Ltd.;
[0056] CSS-88100 microcomputer-controlled electronic universal testing machine, Changchun Testing Machine Research Institute Co., Ltd.
[0057] 1.2 Preparation of ACNP-modified alginate fibers
[0058] Weigh SA powder, dissolve it in distilled water to make a 2.5% (w / v) sodium alginate solution, filter and sterilize it with a 0.45μm filter, and set aside. At the same time, sterilize ACNP at 121℃ for 20min and set aside. Use a 20mL syringe (5# needle) to draw 10mL of 2.5% SA solution, weigh a certain amount of ACNP and dissolve it in the SA solution to make a mixed solution. Use a wet spinning process, adjust the injection pump flow rate (1000μl / min) to flow the mixed solution into a 1.5% (w / v) calcium chloride solution for calcification for 15min, wash twice with distilled water, and make alginate fibers.
[0059] According to the mass ratio of ACNP:SA solution, alginate fibers with ACNP / SA ratios of 0%, 2%, 4%, and 8% were prepared, as shown in Table 1.
[0060] Table 1 Formula of ACNP / SA composite fiber
[0061] sample Weight ratio (ACNP:SA solution) SA content 0%ACNP / SA 0:100 2.5% 2%ACNP / SA 2:100 2.5% 4%ACNP / SA 4:100 2.5% 8%ACNP / SA 8:100 2.5%
[0062] 1.3 Physical characterization of ACNP / SA composite fibers
[0063] 1.3.1 Scanning electron microscopy (SEM): The fibers were freeze-dried for 24 h and then observed using a scanning electron microscope (SEM) with an accelerating voltage of 2 kV.
[0064] Alginate fibers with different ACNP mass ratios were observed under an inverted microscope, e.g. Figure 1 , where Figures a, b, c and d correspond to 0% ACNP / SA, 2% ACNP / SA, 4% ACNP / SA, and 8% ACNP / SA, respectively. It can be seen that the light transmittance of alginate fibers deteriorates with the increase of ACNP concentration. When 8% alginate fibers are added and observed under a 100× optical microscope, no light is transmitted. Figure e corresponds to the image of 8% ACNP / SA at a magnification of 200. When observed under 200×, a small amount of light is still transmitted, but the aggregation of ACNP is also observed (Figure e). Therefore, when alginate fibers are used as medical materials for encapsulating cells, the amount of ACNP added should not exceed 8%.
[0065] The surface morphology of the prepared ACNP / SA composite fibers was observed under an inverted microscope. Figure 2, where Figures a, b, c, and d correspond to 0% ACNP / SA under an inverted microscope at 10×, 0% ACNP / SA under a scanning electron microscope, 2% ACNP / SA under an inverted microscope at 10×, and 2% ACNP / SA under a scanning electron microscope, respectively. It can be seen that there are longitudinal grooves on the surface of the ACNP / SA composite fiber without adding ACNP, while no grooves are observed on the ACNP / SA composite fiber with added ACNP, and the smoothness is good. The characteristic of traditional wet spinning is that the spinning solution directly enters the coagulation bath through the nozzle for coagulation and molding. This molding process often leads to surface groove defects of the fiber, which becomes one of the main factors restricting the mechanical properties of the fiber. In this study, no fiber groove defects were observed after adding a small amount of ACNP, which may be one of the reasons for the improvement of mechanical properties measured in subsequent studies.
[0066] The 0% ACNP / SA and 2% ACNP / SA composite fibers were freeze-dried, and the surfaces were treated with gold spraying. Then, the fiber surfaces were observed with a scanning electron microscope. Figure 2 In the figure, at the same magnification, the surface structure of 0% ACNP / SA fiber is relatively uniform and dense, with small holes evenly distributed on the surface (Figure b). The surface pores of 2% ACNP / SA fiber are larger, and ACNPs are inlaid on the surface of the fiber membrane in a patchwork manner (Figure d), which has a supporting effect on the capsule pores. This structure is conducive to improving the adsorption and permeability of the fiber.
[0067] 1.3.2 Test of ACNP / SA composite fiber diameter: randomly selected prepared alginate fibers, and the cross-sectional diameters of each alginate fiber at three distances were tested under an inverted microscope to obtain the average value D (mm). The results are shown in Table 2.
[0068] 1.3.3 Test of tensile properties of ACNP / SA composite fibers: Referring to the national standard GB / T7689.5-2001, the composite fibers were tested for elongation at break and stress at break using a universal testing machine. The experimental conditions were set to test at room temperature with a tensile speed of 20 mm / min. Elongation at break (Stretch) is defined as: Stretch = (L-L0) / L0×100%. Where L0 is the initial length, and L is the length at tensile break (unit: mm). Fracture stress (Fracture Stress) is defined as: σ = P / A. Where P is the breaking strength (unit N); A is the cross-sectional area (unit m 2 ).
[0069] 1.3.3.1 Elongation at break:
[0070] The fiber formed by pure sodium alginate is hard and brittle, with low elongation at break, and is prone to breakage during processing and use. This study tested the elongation at break of the prepared composite fiber, and each composite fiber was sampled and measured 5 times for data analysis. The results are shown in Table 2. It can be seen that when the ACNP addition amount is 2%, the elongation at break of the prepared ACNP / SA composite fiber is 80.2% higher than that of the alginate fiber without addition. This shows that the addition of an appropriate amount of ACNP plays an important role in improving the mechanical properties of alginate fibers.
[0071] Table 2 Effect of nano-activated carbon on elongation at break of alginate fiber
[0072]
[0073] **P<0.01, compared with the same conditions without ACNP.
[0074] 1.3.3.2 Fracture stress:
[0075] The breaking stress indicates the maximum tensile force that the fiber cross-sectional area can withstand. It is a common indicator of the relative strength of various materials and one of the indicators for measuring the tensile strength of fibers. In this study, a universal testing machine was used to apply axial tension to the sample for tensile testing, and the breaking strength of the sample was measured to calculate the breaking stress of the fiber. As can be seen from Table 3, the breaking stress of the alginate composite fiber was improved after adding ACNP. The ACNP / SA composite fiber with an addition of 2% increased by 42.5%. When the content of ACNP was increased, the breaking stress did not continue to increase. The experiment measured that when 4% was added, the breaking stress only increased by 16.2%.
[0076] Table 3 Effect of nano-activated carbon on the fracture stress of alginate fiber
[0077]
[0078]
[0079] In summary, the addition of an appropriate amount of ACNP (0-2%) can improve the mechanical properties of alginate fibers, such as elongation at break and breaking stress. However, the mechanical properties did not increase with the continuous increase of ACNP (4%) (see Table 2 and Table 3). The possible reason is that the hydrophilic groups such as hydroxyl and carboxyl groups on the surface of ACNP can covalently bind to the hydroxyl groups of the SA molecular structure. When the content of ACNP in the spinning solution is low, ACNP and SA gel form a uniform grid, which can effectively transmit the force exerted on SA, thereby improving the toughness of the composite fiber. However, after the proportion of ACNP increases, ACNP agglomerates in the SA matrix, which also reduces the cross-linking density of the SA molecules themselves, destroys the ordered grid structure, weakens the transmission effect between ACNP and SA matrix, and increases brittleness, which ultimately leads to the mechanical properties of ACNP / SA composite fibers no longer increasing but gradually decreasing. Therefore, the addition of a small amount of ACNP is beneficial to the hydrophilicity of the fiber, increases the elongation performance, and avoids the adverse effects of swelling on mechanical properties.
[0080] 1.3.4 Test of the swelling rate of ACNP / SA composite fibers: The swelling rate (SR) is used to describe the water absorption capacity of the gel. A certain amount of fiber was dried in a vacuum oven at 50°C for 24 hours and then weighed (Wd). Then the dried sample was immersed in 50ml of physiological saline at a constant temperature of 37°C, taken out once every 20 minutes, and the surface moisture was absorbed and weighed (Ws), until the mass no longer increased and reached a balanced swelling state. The swelling rate (SR) was calculated according to the formula: SR = (Ws-Wd) / Wd to calculate the weight gain rate. After measuring three parallel samples for each sample, data analysis was performed.
[0081] Swelling rate is one of the important evaluation indicators of the hydrophilicity of biomaterials. The higher the swelling rate, the better the hydrophilicity of the material, which is conducive to the diffusion of substances, the entry of nutrients required by cells in the material and the discharge of metabolic products. However, a higher swelling rate will reduce the mechanical properties of the material, and it is easy to fall off when used in the body, and it is not completely recovered and remains in the body, causing potential safety risks. Therefore, it is necessary to explore the swelling properties of ACNP / SA composite fibers. Figure 3It can be seen that when the ACNP addition amount is 2%, the swelling rate of ACNP / SA composite fiber is the largest. The possible reason is that a small amount of ACNP added can play the role of supporting the skeleton, reduce the cross-linking degree of SA molecules themselves, and the free hydrogen bonds of SA combine with water molecules to improve the water absorption performance. In addition, the highly developed pore structure of activated carbon may provide a rich internal surface area for the fiber. Its surface contains hydrophilic functional groups and ionic ash. The hydrophilic groups improve the hydrophilicity of the gel, while the ionic ash increases the internal and external osmotic pressure difference, making the alginate fiber swell higher in physiological saline than pure SA. However, with the further increase in the amount of activated carbon, such as increasing to 4%, the rigid activated carbon particles produce an aggregation and extrusion effect, which destroys the basic grid structure, resulting in a decrease in its liquid absorption capacity and a decrease in the swelling rate. In addition, after the addition of ACNP, the time it takes for the composite fiber to reach the equilibrium swelling rate becomes shorter ( Figure 3 ), indicating that the anti-swelling performance of ACNP / SA composite fibers was improved in the later stage. The possible reason for the rapid swelling in the early stage was the skeleton effect of ACNP, which made the fiber pores larger and facilitated the entry of liquid to quickly reach equilibrium.
[0082] In summary, the addition of a small amount of ACNP (0-2%) is beneficial to the hydrophilicity of the fiber, increases the elongation performance, and avoids the adverse effects of swelling on the mechanical properties.
[0083] 1.4 Study on biocompatibility of ACNP / SA composite fibers
[0084] 1.4.1 Biostability test: 2 cm of prepared alginate fiber was measured, 1 mL of 10% FBS DMEM medium was added, and placed in a carbon dioxide medium at 37°C for 21 days. The morphological changes of the fiber were observed on the 0th day, the 7th day, the 14th day and the 21st day, and the absorbance value of the fiber extract at 490 nm was tested. 1 mL of 10% FBS DMEM medium was used as a blank control. The results are shown in Table 4.
[0085] Table 4 Absorbance values of different ACNP / AS fibers on day 0, day 7, day 14 and day 21
[0086] concentration 0d 7d 14d 21d Blank 0.131±0.00259 — — — 0% 0.131±0.00224 0.188±0.00308 0.258±0.0354 0.322±0.00567 2% 0.132±0.00205 0.176±0.00893 0.220±0.0378* 0.239±0.00904** 4% 0.130±0.0328 0.187±0.00687 0.338±0.0709** 0.416±0.0209**
[0087] **P<0.01, compared with the same conditions without ACNP.
[0088] As shown in Table 4, as time goes by, the absorbance values of the extracts in each group gradually increase, indicating that alginate fibers will continue to leach more unknown substances into the culture medium. Comparing the three extract groups, on the 7th day, the difference in absorbance values was not significant, but on the 14th and 21st days, the 4% group was significantly higher than the other two groups, while the 2% group was the smallest, with significant differences. The above results show that the addition of 2% ACNP promotes better biostability of alginate fibers.
[0089] 1.4.2 Cytotoxicity test: The cytotoxicity test of ACNP / SA composite fiber adopts the extraction method. ACNP / SA composite fiber is dried in a drying oven at 50℃ for 24h, added with complete culture medium and soaked for 24h, and the fiber is removed to obtain the extraction culture medium. At the same time, the density of MIN6 cell suspension is adjusted to 5×10 3 / ml, inoculated on a 96-well plate, 100μL per well, and placed in a 37°C, 5% CO2 incubator for 24h. Aspirate the old culture medium and replace it with a new extract culture medium. The control group without the extract was cultured in a 37°C, 5% CO2 incubator for 24-96h, and 5 replicate wells were made for each sample. Take out the cell culture plate at 24h, 48h, and 96h, add 100μL of 10% CCK8 culture medium to each well, place it in a cell incubator for 1h, and take the supernatant to test the absorbance value at 450nm using an enzyme marker.
[0090] Theoretically, sodium alginate is a natural polysaccharide with good biocompatibility, and nano-activated carbon is an inert carbon material with good biocompatibility. Both are medical materials approved by CFDA. The fibers prepared after compounding are highly safe and have good cell compatibility. In order to evaluate the biocompatibility and application potential of the prepared ACNP / SA composite fibers, the CCK-8 method was used in the experiment to detect the toxicity of the composite materials to MIN6 cells. The OD value is used to characterize the cell survival rate. The higher the OD value, the higher the cell survival rate. During the cell culture process, after the cells adapt, the cell number will increase over time, and the viability will increase. Figure 4 As shown, over time, 0% ACNP / SA leaching solution culture affects the proliferation of MIN6 cells, and the possible reason is that the 2.5% alginate fiber leaching solution has a growth inhibitory effect on MIN6. In this experiment, compared with alginate fibers, after adding 2% and 4% concentrations of ACNP to the alginate fibers, the leaching solution showed friendly characteristics of supporting the growth of MIN6 cells, eliminating the adverse effects of alginate gel materials on cells. On the 1st, 2nd and 4th day after inoculation, there was no significant difference in cell viability between the control group and the ACNP-added group, which shows that the ACNP / SA composite fiber is non-toxic to cells in vitro. Therefore, it can be considered that the ACNP / SA composite fiber has good cell compatibility and biosafety, and can be used as a medical material for encapsulating cells.
[0091] Example 2, preparation of ACNP / SA composite fibers:
[0092] The same raw materials, equipment and preparation method as in Example 1 were used to prepare and test products with different content ratios, and the physical characteristics of ACNP / SA composite fibers were observed, and the fiber diameter, tensile properties, biocompatibility and cytotoxicity were measured. The results are summarized in Table 5:
[0093] Table 5 Effect of nano-activated carbon in composite fibers on elongation at break of ACNP / SA composite fibers
[0094]
[0095]
[0096] The above experimental results show that adding ACNP with a mass ratio of 2% (ACNP:SA) to SA with a concentration of 2.5% and wet spinning in a 1.5% CaCl2 coagulation bath can prepare ACNP / SA composite fibers with the best mechanical properties and biocompatibility. The addition of ACNP can improve the groove defect problem of sodium alginate fiber and help improve the mechanical properties of the fiber. The addition of a small amount (0%-2%) of ACNP is beneficial to the hydrophilicity of the fiber and increases the mechanical properties. The elongation at break is increased by up to 80.2%, and the breaking stress is increased by 42.5%, avoiding the adverse effect of fiber swelling on mechanical properties. The addition of 2% ACNP promotes better biostability and lower cytotoxicity of sodium alginate fiber. ACNP / SA composite fibers have good mechanical properties and biocompatibility, and have development and application value in the field of medical materials.
[0097] The sodium alginate composite fiber containing nano-activated carbon provided by the present invention can be used to encapsulate pancreatic islet cells for the treatment of diabetes, or to encapsulate thyroid (para) gland cells to treat patients with thyroidectomy, provide a support structure for pancreatic islet cells or thyroid (para) gland cells, simulate the microscopic and macroscopic environment of natural pancreatic islets or thyroid (para) glands, and form an immune isolation barrier between the implanted cells and the body. The present invention provides a new composite fiber material with good mechanical properties, biocompatibility, better biostability and lower cytotoxicity for encapsulating cells.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing sodium alginate composite fibers containing nano-activated carbon, characterized in that: Weigh sodium alginate powder, dissolve it in distilled water to prepare a 2.5% w / v sodium alginate solution, filter and sterilize it with a 0.45 μm filter, and set it aside; at the same time, sterilize nano-activated carbon at 121° C. for 20 min, and set it aside; weigh the sterilized nano-activated carbon and dissolve it in the sodium alginate solution to prepare a mixed solution, the weight ratio of the nano-activated carbon to the sodium alginate solution is 2:100, and adopt a wet spinning process, adjust the injection pump flow rate to 1000 μl / min, and let the mixed solution flow into a 1.5% w / v calcium chloride solution for calcification for 15 min, and wash it twice with distilled water to prepare sodium alginate composite fibers; The particle size of the nano activated carbon is 50-300 nm.
2. The use of the sodium alginate composite fiber containing nano-activated carbon obtained in claim 1, characterized in that: For cell encapsulation, the cells include but are not limited to pancreatic islet cells, thyroid cells and parathyroid cells.
Citation Information
Patent Citations
Calcium alginate fiber and preparation method thereof
CN103820880A
Modified biomass fiber and preparation method thereof
CN104963031A
Preparation method of activated carbon-carrying alginate fiber
CN108588901A